PERBANDINGAN KUALITAS HIDUP PASIEN YANG MENJALANI TERAPI HEMODIALISA BERDASARKAN AKSES VASKULAR - Fiora Ladesvita; nanda syifa (Indonesian Journal of Health Development, 2022)
In patients CKD undergoing hemodialysis, it will have an impact on the psychological and physical conditions which will result in a decrease in the patient's quality of life. Hemodialysis requires long-lasting vascular access with minimal complications. Because vascular access has a risk of complications that will worsen the patient's life situation. So it is necessary to choose vascular access for hemodialysis so that it can improve the patient's quality of life. This study aims to compare the quality of life of patients undergoing hemodialysis based on vascular access. This study used a quantitative research design and a cross sectional research method with the Mann Whitney test to determine the differences in the specified variables. The sample collection technique used is probability sampling as many as 101 respondents. The instrument used in this study was Kidney Disease Quality of Life (KDQOL-SF36). The results showed that there were differences in 3 domains of quality of life between AVF and CDL, namely the symptom and problem domains, burden due to kidney disease, SF-12 physical health (p-value: 0.040; 0.050; 0.008 which means P<0.05). In addition, the mean quality of life in AVF is greater than in CDL. This research is expected to add and increase knowledge about the quality of life of patients undergoing hemodialysis therapy based on vascular access. Keywords: Vascular access, Quality of life, Hemodialysis.